Rumen Microbiology: From Evolution to Revolution - Puniya, Anil Kumar; Singh, Rameshwar; Kamra, Devki Nandan (Springer India : Imprint: Springer, 2015)
This book offers an in-depth description of different groups of microbes (i.e. bacteria, protozoa, fungi and viruses) that exist in the rumen microbial community, and offers an overview of rumen microbiology, the rumen microbial ecosystem of domesticated ruminants, and rumen microbial diversity. It provides the latest concepts on rumen microbiology for scholars, researchers and teachers of animal and veterinary sciences. With this goal in mind, throughout the text we focus on specific areas related to the biology and complex interactions of the microbes in rumen, integrating significant key issues in each respective area. We also discuss rumen manipulation with plant secondary metabolites, microbial feed additives, utilization of organic acids, selective inhibition of harmful rumen microbes, and 'omics' approaches to manipulating rumen microbial functions. A section on the exploration and exploitation of rumen microbes addresses topics including the current state of knowledge on rumen metagenomics, rumen: an underutilized niche for industrially important enzymes, and ruminal fermentations to produce fuels. We next turn our attention to commercial applications of rumen microbial enzymes and to the molecular characterization of euryarcheal communities within an anaerobic digester. A section on intestinal disorders and rumen microbes covers acidosis in cattle, urea/ ammonia metabolism in the rumen, and nitrate/ nitrite toxicity in ruminant diets. Last, the future prospects of rumen microbiology are examined, based on the latest developments in this area. In summary, the book offers a highly systematic collection of essential content on rumen microbiology.